Recommendations for Selection of New Students at Madrasah Aliyah Negeri Sidoarjo Using the Analytical Hierarchy Process – Weighted Product - Muhammad Rizky Abdul Gofur; Ahmad Afif Supianto; Nanang Yudi Setiawan (Journal of Information Technology and Computer Science, 2022)
Madrasah Aliyah Negeri (MAN) Sidoarjo is the only Madrasah Aliyah in Sidoarjo Regency under the Ministry of Religion. Many applicants always fill every year MAN Sidoarjo compared to the number of admission quotas, so it takes the suitable method in selecting new students. However, until now, MAN Sidoarjo has not found the correct method in determining new students, and the school has not used the data of new students as best as possible. In solving the problem, the methods used are AHP (Analytical Hierarchy Process) and Weighted Product. The AHP method is used in determining the weight of the criteria used, while the Weighted Product method is used to assess the quality of the recommendation data. The data used in this study is the data of admission of new students man Sidoarjo school year 2020/2021 with a total of 875 data. The expected result is 267 prospective students who qualified, 40 candidates, declare in reserve, and 568 candidates did not qualify. The results conduct test agreement using the coefficient kappa generated value 0.837 (excellent). Data-limited visualizations do with Google Data Studio in a dashboard of graphs and cards. Usability testing conduct using the System Usability Scale with a value of 82.5 shows the dashboard successfully deploy in the registration selection program of new students of MAN Sidoarjo.